Internal Parasites of Pigs and Worm Control Practices in Bamboutos, Western Highlands of Cameroon - Marc K. Kouam; Fabrice D. Ngueguim; Vaia Kantzoura (Journal of Parasitology Research)
Internal parasites are limiting factors to successful, sustainable livestock production. Knowledge on how they are dealt with is important to prevent resistance to anthelmintics. The aim of this study was to describe the internal parasitism of indoor pigs in Bamboutos Division in Cameroon, as well as the attendant worm control practices. Thus, 324 pigs from 50 small scale farms were sampled for feces which were qualitatively and quantitatively examined for parasite eggs, cysts, or oocysts. Data on worm control practices were also collected. The overall prevalence was 74.7% (95 % Confidence Interval (CI): 69.6–79.3%) and the overall mean egg/oocyst per gram of feces (epg/opg) was 304.1±1218.0. The following parasites were found: Strongylid parasites (58.6%; epg= 105.0±134.7); Coccidia (26.9; opg=517.2± 1862.1); Strongyloides ransomi (25.9%; epg=61.9± 40.8); A. suum (3.7%. epg=50±0); Metastrongylus sp (0.9%; epg=50±0); Trichuris suis (0.9%; epg=50±0); and Macracanthorhynchus hirudinaceus (0.62%; epg=50±0). Single to septuple infestations occurred. The majority of farmers resorted to modern veterinary services (64%) and mostly used conventional drugs (88%). Internal parasitism was associated with the person in charge of animal health, the implementation of a prophylaxis program on the farm, and the annual deworming frequency. The implementation of a prophylaxis program significantly reduced the overall egg/oocyst load while high treatment frequency (more than thrice a year) did not, indicating that prophylaxis measures such as general hygiene must be reinforced in pig herds in the country, and the treatment frequency reduced as much as possible to prevent the selection of anthelmintic resistance.